Recombinant Human Myelin-Associated Glycoprotein Promoter Drives Selective AAV-Mediated Transgene Expression in Oligodendrocytes - von Jonquieres, Georg; Fröhlich, Dominik; Klugmann, Claudia B.; Wen, Xin; Harasta, Anne E.; Ramkumar, Roshini; Spencer, Ziggy H. T.; Housley, Gary D.; Klugmann, Matthias (Frontiers in Molecular Neuroscience, 2016)
Leukodystrophies are hereditary central white matter disorders caused by oligodendrocyte dysfunction. Recent clinical trials for some of these devastating neurological conditions have employed an ex vivo gene therapy approach that showed improved endpoints because cross-correction of affected myelin-forming cells occurred following secretion of therapeutic proteins by transduced autologous grafts. However, direct gene transfer to oligodendrocytes is required for the majority of leukodystrophies with underlying mutations in genes encoding non-secreted oligodendroglial proteins. Recombinant adeno-associated viral (AAV) vectors are versatile tools for gene transfer to the central nervous system and proof-of-concept studies in rodents have shown that the use of cellular promoters is sufficient to target AAV-mediated transgene expression to glia. The potential of this strategy has not been exploited. The major caveat of the AAV system is its limited packaging capacity of ~5 kb, providing the rationale for identifying small yet selective recombinant promoters. Here, we characterize the human myelin associated glycoprotein (MAG) promoter for reliable targeting of AAV-mediated transgene expression to oligodendrocytes in vivo. A homology screen revealed highly conserved genomic regions among mammalian species upstream of the transcription start site. Recombinant AAV expression cassettes carrying the cDNA encoding enhanced green fluorescent protein (GFP) driven by truncated versions of the recombinant MAG promoter (2.2 kb, 1.5 kb and 0.3 kb in size) were packaged as cy5 vectors and delivered into the dorsal striatum of mice. At three weeks post-injection, oligodendrocytes, neurons and astrocytes expressing the reporter were quantified by immunohistochemical staining. Our results revealed that both 2.2 kb and 1.5 kb MAG promoters targeted more than 95 % of transgene expression to oligodendrocytes. Even the short 0.3 kb fragment conveyed high oligodendroglial specific transgene expression (> 90 %) in vivo. Moreover, cy5-MAG2.2-GFP delivery to the neonate CNS resulted in selective GFP expression in oligodendrocytes for at least eight months. Broadly, the characterization of the extremely short yet oligodendrocyte-specific human MAG promoter may facilitate modelling neurological diseases caused by oligodendrocyte pathology and has translational relevance for leukodystrophy gene therapy.